PENERAPAN STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PRODUK 3i NETWORK DENGAN MENGGUNAKAN ANALISA SWOT (Studi Kasus Pada PT. AJ Central Asia Raya Cabang Semarang) (E-logis : Jurnal Ekonomi Logistik, 2021)
This study discusses marketing strategies that have been approved or carried out at PT.AJ Central Asia Raya Semarang Branch in terms of selling 3i Network products to new customers or retaining old customers using qualitative descriptive research using SWOT analysis. This research was conducted by direct interview method by distributing questionnaires. The population in this study were all employees and director agencies at PT. AJ Central Asia Raya Semarang Branch and the samples used are all employees and director agencies at PT. AJ Central Asia Raya Semarang Branch. Data collection methods used were documentation, questionnaires / questionnaires and qualitative literature research with evidence attached in the appendix. The results of this qualitative study indicate the strategies used by PT. AJ.Central Asia Raya Semarang by using a diversification or innovation strategy. By using the analysis of SAP and ETOP PT. AJ Central Asia Raya Semarang Branch is in a strong internal position and an external position in speculative business. So the company PT.AJ Central Asia Raya Semarang Branch is in an investment position to develop 3i Network products with increasingly aggressive innovations to increase the company's turnover.